Analisis Penggunaan Selenoid 24 VDC Pada Jalur Masuk Membran Terhadap Sistem Kerja Dispenser RO Magna - Teten Dian Hakim; Raihan Zakih (JURNAL ELEKTRO, 2026)
The condition of the raw water path in the RO (Reverse Osmosis) Magna dispenser which does not close completely towards the membrane when the storage tank is full which results in the membrane producing excess product water and reject water resulting in waste of raw water. The use of a 24 VDC selenoid aims to withstand raw water pressure when the storage tank is full. The purpose of this study was to determine the effect produced after installing a 24 VDC selenoid to the membrane. The techniques used in this research are observation and interviews. The function of the 24 VDC selenoid is to hold water in the raw water line that will enter the membrane. The results showed that there was no excessive discharge of reject water when the storage tank was full. From the results of the study it was found that when using a Automatic Shut Off Valve as a water retainer produced as much as 180 ml of reject water per minute, then when using a selenoid as a water retainer, it produced 0 ml of reject water per minute. The use of selenoids to replace the role of Automatic Shut Off Valve as water retainers when the storage tank conditions are full can be said to be successful because the membrane no longer gets raw water pressure. For the next step, you can test similar tools to get comparable and optimal results.